Role of the glycemic level on in the functional state of the myocardium in patients with coronary heart disease and type 2 diabetes mellitus. (14th October 2021) - Kondrat'eva, D; Budnikova, O V; Afanasiev, S A; Akhmedov, S H; Popov, S V
Abstract:  : Clinical studies show that hyperglycemia is significant factor that worsens the prognosis and course of the cardiovascular diseases. At the same time, there is evidence that an increased level of glycemia in patients with type 2 diabetes mellitus (DM2) is associated with a better outcome of cardiovascular complications compared to the same patients, but with a normal level of glycemia. Aim: To investigate the effect of the glycemia level on the functional state of the myocardium in patients with coronary heart disease (CHD) and DM2. Methods: The study included patients with a chronic CHD associated with DM2, who were divided into 2 groups. Group 1 included patients with glycated hemoglobin (HbA1c) <8%, and 2 - patients with HbA1c ≥8%. The function of the heart, according to echocardiography (Echo-KG) and the contractile properties of trabeculae isolated from the right atrial auricle obtained during coronary bypass surgery were studied. To assess the contractile function of the trabeculae, exposure to periods of rest was used [4]. Post-rest inotropic reaction was evaluated. The level of expression of Ca2+-ATPase (SERCA2a) and ryanodine receptors (RyR2) of the sarcoplasmic reticulum (SR) was also determined in the patients ' myocardial samples by immunoblotting. Results: According to the clinical characteristics, the patients of the groups were comparable, including age and duration of the disease of DM2. According to the Echo-KG data, it was found that in patients of group 1, the values of the end systolic and diastolic volumes, the thickness of the interventricular septum and the mass of the myocardium of the left ventricle (LV) were significantly lower in comparison with the corresponding indicators of patients of group 2. The rate of early LV filling (E) was significantly lower in group 1. At the same time, the rate of rapid LV filling did not have significant differences between groups. The amplitude of post-rest contractions of the trabeculae of patients in both groups was potentiated for short periods of rest, but with an increase in the duration of rest periods, it increased significantly only in group 2. After long periods of rest, the post-rest inotropic response of group 1 patient myocardium was not potentiated. As is known, post-rest potentiation characterizes the function of the SR. So, it is indicates better preservation of SR function in patients with HbA1c ≥8%. This statement is confirmed by the data on the expression of Ca2+ - transporting CP proteins SERCA2a and RyR2. Our studies have shown that the expression level of SERCA2a and RyR2 is significantly higher in the myocardium of patients with HbA1c ≥8% compared to patients with HbA1c <8%. Conclusion: In the patients with CHD and DM2, an increased level of HbA1c is associated with better the functional state of the myocardium according to the contractile activity of isolated trabeculae, as well as the whole heart, which associated with higher SERCA2a and RyR2 expression. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Russian Science Foundation